2022
DOI: 10.20473/jfiki.v9i12022.75-81
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking of Active Compound of Lavandula angustifolia Mill Essential Oil against N-methyl-D-aspartate (NMDA) Receptor

Abstract: Background: Lavender oil is widely known to possess a relaxant effect to relieve stress, anxiety, and depression. Linalyl acetate, linalool, geranyl acetate, and β-caryophyllene were the major constituents of lavender oil that potentially act on NMDAR (N-methyl-d-aspartate receptors), and emerging targets in the treatment of depression. Objective: This study aims to predict the binding of lavender compounds to NMDA receptors using an in silico model. Methods: The ligands of the docking study were four major ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, it is still not chosen as the favourable drug-like properties in treating the COVID-19 main protease inhibitor. Furthermore, a recent study by Lisnasari and friends showed that ß-Caryophyllene inside the active compound of Lavandula angustifolia (lavender oil) had a binding energy of -8.02 kcal/mol when docked with N-methyl-D-aspartate (NMDA) receptor [12]. It could be developed as a treatment for depression.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is still not chosen as the favourable drug-like properties in treating the COVID-19 main protease inhibitor. Furthermore, a recent study by Lisnasari and friends showed that ß-Caryophyllene inside the active compound of Lavandula angustifolia (lavender oil) had a binding energy of -8.02 kcal/mol when docked with N-methyl-D-aspartate (NMDA) receptor [12]. It could be developed as a treatment for depression.…”
Section: Resultsmentioning
confidence: 99%